(untitled) (World of finance, 2024)
Introduction. Features of the financing of social protection and social security in conditions of large-scale war include increased spending on military needs, assistance to IDPs, reconstruction of damaged infrastructure facilities, and provision of medical assistance to the injured. On the other hand, martial law can lead to a reduction in spending on social programs due to the redistribution of budget funds to the country’s defense needs. The study of this topic will make it possible to understand how the military conflict affects the financial possibilities of providing social protection and social security for the population of Ukraine, to identify problematic aspects and to look for effective financing strategies in such conditions. The purpose of the article is to reveal the theoretical and practical foundations of the financing mechanism of social protection and social security in Ukraine, to identify possible strategies and prospects for optimizing this system in the face of new challenges. Results. The theoretical foundations of financing social protection and social security in Ukraine are highlighted. The dynamics of budgetary financing of social protection and social security and the structure and composition of expenditures of the State and local budgets for social security and social security are analyzed. The peculiarities of expenditures on social protection and social welfare in the conditions of a large-scale war are highlighted. The main problems were revealed and ways of improving the system of financing social protection and social security were formed. Conclusions. The beginning of a large-scale war on the territory of Ukraine significantly affected the social protection of the population. The hostilities caused an increase in expenses for social assistance, and in the future only an increase in this item of expenses is predicted. In the post-war years, spending on social protection and social security will only increase due to a significant increase in war veterans, persons with disabilities, IDPs affected by the military conflict, as well as citizens who will suffer from economic difficulties and social challenges caused by the war. Therefore, today, an important task for the state is to ensure social protection and social security during such a crisis situation as war, and in the future - comprehensive regulation of the social protection system of Ukraine.